PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS PADA PT TELEKOMUNIKASI INDONESIA TBK PERIODE 2014-2023 - Asiyah; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of Company Size and Leverage both partially and simultaneously on Profitability at PT Telekomunikasi Indonesia Tbk for the 2014-2023 Period. This research method uses quantitative methods. The population used in this study is sourced from the financial data of the official website of PT Telekomunikasi Indonesia Tbk. The sample of this study is financial statement data in the form of balance sheets and profit and loss at PT Telekomunikasi Indonesia Tbk for the period 2014 to 2023. The data analysis used includes classical assumption test, simple linear regression test, multiple linear regression test, determination coefficient test, partial test and simultaneous test. The results of this study based on the classical assumption test did not find variables that deviated from the classical assumptions. These results indicate that the available data has met the requirements for using multiple regression equation models. Based on the t test, it can be seen that partially company size partially has a significant effect on profitability. Leverage has no significant effect on profitability. And simultaneously Company Size and Leverage have a significant effect on Profitability. with a contribution of 60.7%, while the remaining 29.3% is influenced by other factors outside of this study.